2014
DOI: 10.1007/s11920-014-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Eating Disorder Pathology: Common and Unique Features of Successful Eating Disorders Prevention Programs

Abstract: Over the past two decades, the field of eating disorders has made remarkable strides in identifying, evaluating, and disseminating successful prevention programs. The current review identifies and discusses nine distinct eating disorders prevention programs that reduce existing eating disorder pathology or prevent the onset of future pathology. Each program was evaluated in one or more controlled trial with a follow-up period of at least six months. We review the evidence base for these nine successful program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 70 publications
2
70
0
9
Order By: Relevance
“…A large proportion of ED prevention research, either in person or Internet-delivered, has focused on targeted prevention, in which individuals exhibiting eating disorder risk factors are assigned to an intervention (Ciao et al, 2014). A smaller number of studies has examined indicated prevention programs, which aim to reduce symptoms and cease symptom progression among individuals who already present with ED symptoms but do not meet full criteria for diagnosis (Ciao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of ED prevention research, either in person or Internet-delivered, has focused on targeted prevention, in which individuals exhibiting eating disorder risk factors are assigned to an intervention (Ciao et al, 2014). A smaller number of studies has examined indicated prevention programs, which aim to reduce symptoms and cease symptom progression among individuals who already present with ED symptoms but do not meet full criteria for diagnosis (Ciao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Those were mainly carried out in schools and addressed the first and second stages according to the stage model (Ciao, Loth, & Neumark-Sztainer, 2014;Stice, Shaw, & Marti, 2007;Treasure et al, 2015;Yager, Diedrichs, Ricciardelli, & Halliwell, 2013). According to Levine and Smolak (2006), schools are highly appropriate settings for the delivery of prevention programs.…”
Section: Prevention Programs and Their Effectsmentioning
confidence: 99%
“…They have potential for sustained interactions with young students in different developmental stages. In systematic and meta-analytic reviews, important features of prevention programs were identified, leading to successful program outcomes (Ciao et al, 2014;Stice & Shaw, 2004;Stice et al, 2007;Yager et al, 2013). Successful programs were theory-driven, interactive, delivered in multiple group sessions by professionals, and targeted at least one eating disorder risk factor.…”
Section: Prevention Programs and Their Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, findings from prevention trials may be flawed with false positive findings. In the literature, over 60 programmes have been identified, most of them with no or just short-lived effects (Ciao, Loth & Neumark-Sztainer, 2014). Hence, the issue has pertinently been raised (Becker et al, 2014) about the feasibility of spending societal money as well as time and energy on disseminating ineffective programmes.…”
Section: From Analytic To Social Epidemiology: An Update and Future Smentioning
confidence: 99%